Negative Pressure within a Liquid-Fluid Interface Determines Its Thickness - Srebnik, Simcha (Langmuir : the ACS journal of surfaces and colloids, 2020)
The density within the interface between two fluid phases at equilibrium gradually changes from that of one phase to that of the other. The main change in density, according to experimental measurements, practically occurs over a finite distance of O [1 nm]. If we assume that the average stress difference within the interface is on the order of magnitude of ambient pressure, then the Bakker equation implies that for a liquid with surface tensions, say ∼50 mN/m, we get an interface thickness of ∼500 nm. This is certainly too big because it contradicts experimental findings. Alternatively, if the thickness is assumed to be O [10 nm] or less, as is usually believed, the average stress difference must be ∼5 × 106 N/m2 or bigger, which is surprisingly high. This paper shows using a few approaches that such a high average stress difference is due to negative stresses in the interface